Preschoolers in the Playground: a pilot cluster randomised controlled trial of a physical activity intervention for children aged 18 months to 4 years - Sally E Barber; Shaheen Akhtar; Cath Jackson; Daniel D Bingham; Catherine Hewitt; Ash Routen; Gerry Richardson; Hannah Ainsworth; Helen J Moore; Carolyn D Summerbell; Kate E Pickett; Claire O'Malley; et al. (NIHR Journals Library, 2015)
Background: The preschool years are considered critical for establishing healthy lifestyle behaviours such as physical activity. Levels of physical activity track through childhood into adulthood and establishing habitual physical activity early in life is therefore vital. Time spent outdoors is associated with greater physical activity and playground interventions have been shown to increase physical activity in school-aged children. There are few preschool, playground-based interventions and these have given inconclusive results. A report published by the UK's Chief Medical Officer (CMO) highlighted the need for new interventions to promote movement in the early years (0-5 years). Objectives: This study aimed to undertake a pilot cluster randomised controlled trial (RCT) of an outdoor playground-based physical activity intervention for parents and their children aged from 18 months to 4 years (Preschoolers in the Playground or PiP) and to assess the feasibility of conducting a full-scale cluster RCT. Design: The study was a two-armed pilot cluster RCT with economic and qualitative evaluations. Participants were randomised on a 1 : 1 basis to the PiP intervention (n = 83) or usual practice (control; n = 81). Setting: Bradford, West Yorkshire, UK. Participants: Children aged from 18 months to 4 years. Intervention: The PiP intervention is grounded in behavioural theory (social cognitive theory) and is in accordance with CMO guidance for physical activity in the early years. It is informed by existing literature and data collected from focus groups with parents. The intervention was delivered in primary school playgrounds. Six 30-minute PiP sessions per week were available for 30 weeks; families were encouraged to come to three a week. The 10-week initiation phase was facilitated by a member of school staff and the maintenance phase was unsupervised. Main outcome measures: Recruitment and retention of schools and families to the trial were the main outcome measures. The acceptability of trial procedures and the intervention, the feasibility of collecting health outcome data and the fidelity of the implementation of the intervention were also evaluated. A preliminary assessment of cost-effectiveness and a sample size calculation for a full trial were conducted. Results: In total, 37% of schools and 48% of parents approached agreed to take part. Levels of retention were good at 10 and 52 weeks' follow-up (82.3% and 83.5% respectively). Both the trial procedures and the intervention were acceptable. However, attendance was low during the autumn and winter/spring initiation phases but somewhat better in the summer initiation phase. Attendance was poor throughout all maintenance phases. The accelerometry protocol for measuring physical activity requires modification. The fidelity of intervention implementation was good (81% adherence). The intervention was borderline cost-effective. A sample size of 600 children from 38 schools is required for a full trial. Conclusion: A full RCT of the PiP intervention is feasible. The PiP intervention requires some modification, for example running the intervention during the summer term only, but was found to be acceptable to schools and families. Trial registration: Current Controlled Trials ISRCTN54165860. Funding: This project was funded by the NIHR Public Health Research programme and will be published in full in Public Health Research; Vol. 3, No. 5. See the NIHR Journals Library website for further project information.